2019
DOI: 10.1002/jbmr.3948
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Transmission Ratio Distortion of GNAS Loss-of-Function Mutations

Abstract: Pseudohypoparathyroidism type 1A (PHP1A) and pseudopseudohypoparathyroidism (PPHP) are two rare autosomal dominant disorders caused by loss-of-function mutations in the imprinted Guanine Nucleotide Binding Protein, Alpha Stimulating Activity (GNAS) gene, coding G s α. PHP1A is caused by mutations in the maternal allele and results in Albright's hereditary osteodystrophy (AHO) and hormonal resistance, mainly to the parathormone (PTH), whereas PPHP, with AHO features and no hormonal resistance, is linked to muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
(62 reference statements)
2
13
0
1
Order By: Relevance
“…2). Similar to the findings in PHP1A/PPHP females, ( 26 ) the odds of transmitting the mutant, not the wild‐type, STX16/GNAS allele to the next generation is therefore approximately 2:1.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…2). Similar to the findings in PHP1A/PPHP females, ( 26 ) the odds of transmitting the mutant, not the wild‐type, STX16/GNAS allele to the next generation is therefore approximately 2:1.…”
Section: Resultssupporting
confidence: 72%
“…A recent study had revealed that females affected by PHP1A or PPHP are more likely to transmit the allele with disease‐causing GNAS mutation instead of the normal allele to their children, particularly if the genetic defect was predicted to severely reduce or abolish Gsα function. ( 26 ) We now sought to determine whether a similar TRD can be observed also for mutations that reduce Gsα function through LOM at GNAS exon A/B alone or LOM at all three maternal DMRs. We therefore investigated first all available members of kindred F that had facilitated the initial identification of genetic locus for AD‐PHP1B and the subsequent discovery of the 3‐kb STX16 deletion on the maternal allele as the most frequent cause of this disorder.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations